TMT-Based Quantitative Proteomics Analysis Reveals the Panoramic Pharmacological Molecular Mechanism of β-Elemonic Acid Inhibition of Colorectal Cancer - Xia, Yong; Yang, Jinfan; Li, Chao; Hao, Xiaopeng; Fan, Huixia; Zhao, Yuyang; Tang, Jinfu; Wan, Xiufu; Lian, Sen; Yang, Jian (Frontiers in Pharmacology, 2022)
Colorectal cancer (CRC) is one of the most common cancers worldwide but has limited available therapeutic methods; therefore, there is a need to develop highly efficient prevention and treatment strategies. Here, we investigated the anti-cancer activity of β-elemonic acid (EA) in CRC in vitro and in vivo. Our results showed that EA inhibited cell proliferation and migration in the CRC cell lines SW480 and HCT116. Moreover, EA significantly suppressed the growth of transplanted colorectal tumors in nude mice. Interestingly, high-throughput tandem mass tag (TMT)-based quantitative proteomics indicated that EA mainly targets tumor mitochondria and attenuates the translation of 54 mitochondrial ribosome proteins, many of which are discovered significantly upregulated in clinical CRC patients. More interestingly, EA at a low concentration (lower than 15 μg/ml) repressed the cell cycle by downregulating CDK1, CDK6, and CDC20, whereas at a high concentration (higher than 15 μg/ml), caused a non-apoptotic cell death – ferroptosis via downregulating ferritin (FTL) and upregulating transferrin (TF), ferroxidase (CP), and acyl-CoA synthetase long-chain family member 4 (ACSL4). This is the first report on the panoramic molecular mechanism of EA against CRC, which would make great contributions to developing a novel drug for colorectal cancer therapy.